PH-dependent norfloxacin degradation by E+-ozonation: Radical reactivities and intermediates identification. (20th August 2020) - Wang, Hui; Cheng, Zhaowen; Zhu, Nanwen; Yuan, Haiping; Lou, Ziyang; Otieno, Peter; Li, Wei
Abstract: Norfloxacin (NOR), a largely synthetized fluoroquinolone antibiotic, is frequently detected in aquatic environment and is resistant to conventional wastewater treatment process. In this study, a typical green technology, i.e., E + -ozonation, was employed and the effect of pH on NOR degradation was investigated. Two-pronged influences of pH were considered here, which were ionic forms of NOR and generation of reactive species. NOR 0, - (pH 11) degradation rate for E + -ozonation in rapid stage reached 91.5%, which was much higher than NOR +, 0 (pH 3, 57.9%) and NOR +, - (pH 7.8, 70.7%). The apparent rate constants for the degradation of NOR +, 0, NOR +, -, and NOR 0, - in rapid stage was 0.007, 0.011 and 0.022 s −1, respectively, as protonation of amine group presenting in the piperazinyl ring in NOR +, 0 resulted in a decrease in its reactivity towards radicals. Obviously, OH was greatly improved with the concentration of 5.7 × 10 −5  mg/L at pH 11, which was twice higher than that generated at pH 3 due to cathodic O2 reduction. Cl − in the solution could be activated into ClO − and HClO from anode and reacted with OH into Cl and ClO under alkaline conditions for further improving the oxidative ability in this system. In addition, twenty five transformation intermediates were identified altogether, but a significantly different pathways were perceived for the degradation of NOR with different ionic forms. Graphical abstract: Image 1 Highlights: pH affects ionic forms of norfloxacin (NOR) and reactive species in E + -ozonation. NOR 0, - removal reached 91.5% in 120 s much higher than that of NOR +, 0 and NOR +, - . OH was greatly improved and Cl./ClO were emerged under alkaline conditions. Fifteen of 25 transformation intermediates have been identified for the first time. A significantly different pathways were perceived for different NOR species.